Toy story : entering the realm of toy collectors - Mark Angelo Orjalo et.al. 4 0 16; 5 (2017)
ABSTRACT: This qualitative study aimed to delve on toy collector's feelings, thoughts, and experiences. Guided by Ryan and Deci's Self-Determination Theory, the researchers discovered how toy collecting affects a toy collector's life. This study employed the Descriptive Phenomenology, which is concerned on the lived experiences of the participants. The participants were selected according to their age, the length of time they have been collecting, and the volume of collectibles they have. In conducting this study, the researchers used interview questions as an instrument to gather data. And lastly, the researchers utilized Giorgi's Empirical Phenomenological Model in organizing the collected data. The results of this study showed that the main reason why adults engage to toy collecting was their motivation to achieve happiness and satisfaction.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2